2023
DOI: 10.3389/fonc.2023.1191093
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between women’s body mass index and breast cancer outcomes was U-shaped

Abstract: BackgroundSeveral studies have analyzed the relationship between body mass index (BMI) and the prognosis of breast cancer (BC). However, whether their relationship is linear or curvilinear remains unclear. This cohort study examined the specific relationship between BMI and BC outcomes.MethodsThis retrospective cohort study included 1049 BC patients from March 7, 2013 through December 31, 2019 in a hospital. Kaplan-Meier curves, multivariate Cox proportional models, and restricted cubic spline (RCS) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Over the past few years, several studies have shown that a high FFA level was an independent risk factor for several types of malignancy, such as lung cancer, gastric cancer, thyroid cancer, colon cancer, rectal cancer, ovarian cancer (Zhang et al 2020b(Zhang et al , 2022. Recently, a retrospective analysis of 1049 cases of breast cancer indicated that BMI was an independent prognostic factor for BC, and had a U-shaped relationship with OS and breast cancer-speci c survival (BCSS) (Wei et al 2023). Although the underlying mechanisms of BMI and BC outcomes have been well studied, the relationship between serum FFA levels and BC prognostic curves in different BMI subgroups remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, several studies have shown that a high FFA level was an independent risk factor for several types of malignancy, such as lung cancer, gastric cancer, thyroid cancer, colon cancer, rectal cancer, ovarian cancer (Zhang et al 2020b(Zhang et al , 2022. Recently, a retrospective analysis of 1049 cases of breast cancer indicated that BMI was an independent prognostic factor for BC, and had a U-shaped relationship with OS and breast cancer-speci c survival (BCSS) (Wei et al 2023). Although the underlying mechanisms of BMI and BC outcomes have been well studied, the relationship between serum FFA levels and BC prognostic curves in different BMI subgroups remains unknown.…”
Section: Introductionmentioning
confidence: 99%